2020
DOI: 10.1002/htj.21872
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐mass flux and Cattaneo–Christov heat flux through a Prandtl non‐Newtonian nanofluid in Darcy–Forchheimer porous space

Abstract: The Darcy-Forchheimer Prandtl fluid flow due to moving sheet is described here. The familiar energy transfer model, namely, the Cattaneo-Christov model of heat transportation, is adopted under thermal radiation phenomenon. The Prandtl non-Newtonian nanofluid is accounted as a functioning fluid. The functioning fluid flows in Darcy-Forchheimer porosity space. The boundary-layer and similarity variables are executed to reframe the mathematical expressions into simplified and single independent variable. Numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Going along with Mohamed et al 24 and Salleh et al, 26 the dimensionless changeable such as: normalϵ=xd,normalζ=yitalicGr14d,r=rd,normalθ=ѱνε(italicGr)14,h=d2νεitalicGr34normalӨ,normalϑ=TTTwT,normalϕ=CCCwC.normalϕ=normalCCCwC…”
Section: Mathematical Formulationmentioning
confidence: 95%
See 1 more Smart Citation
“…Going along with Mohamed et al 24 and Salleh et al, 26 the dimensionless changeable such as: normalϵ=xd,normalζ=yitalicGr14d,r=rd,normalθ=ѱνε(italicGr)14,h=d2νεitalicGr34normalӨ,normalϑ=TTTwT,normalϕ=CCCwC.normalϕ=normalCCCwC…”
Section: Mathematical Formulationmentioning
confidence: 95%
“…The effect of viscous dissipation in nanofluid on circular cylinder has been evaluated by Mohamed et al 24 They conclude that the Eckert number gives no influence on thermal and velocity boundary layer thicknesses. But very recently Fatunmbi and Okoya, 25 Reddy et al, 26 and Reddy and Ferdows 27 reported that the presence of Eckert number exhibits increasing behavior on temperature frontier layer thicknesses. Since thermal volumetric expansion increases because of buoyancy force which reduces the density of fluid results the temperature distribution growth.…”
Section: Introductionmentioning
confidence: 99%
“…Shehzad et al 43 published his latest study to investigate about behavior of nanoparticles Fe 2 SO 4 and Ti 6 Al 4 v in a micropolar fluid. Reddy et al 44 made an investigation related to Cattaneo–Christov heat flux and zero‐mass flux through porous space. In another study, He 45 discusses the effect of thermal radiation and altitude on a MHD micropolar fluid.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the heat transfer rate augments with the electro‐osmotic force. Notable works on the non‐Newtonian fluid across distinct geometries are found in References [9‐15].…”
Section: Introductionmentioning
confidence: 99%